Risk assessment for Thai population: Benchmark dose of urinary and blood cadmium levels for renal effects by hybrid approach of inhabitants living in polluted and non-polluted areas in Thailand - Nishijo M. (BioMed Central Ltd., 2014)
Background: The aim of the present study was to estimate the benchmark doses (BMD) for renal effects for health risk assessment of residents living in Cd-polluted and non-polluted areas in a Thai population. Methods. The study participants consisted of inhabitants aged 40 years or older who lived in a non-polluted area (40 men and 41 women) and in the environmentally polluted Mae Sot District (230 men and 370 women) located in northwestern Thailand. We measured urinary and blood cadmium (Cd) as markers of long-term exposure and urinary β2-microglobulin (β2-MG) and N-acetyl-β-D-glucosaminidase (NAG) as renal tubular effect markers. An updated hybrid approach was applied to estimate the benchmark doses (BMD) and their 95% lower confidence limits (BMDL) of urinary and blood Cd for Cd-induced renal effects in these subjects. BMD and BMDL corresponding to an additional risk (BMR) of 5% were calculated with the background risk at zero exposure set to 5% after adjusting for age and smoking status. Results: The estimated BMDLs of urinary Cd for renal effect markers were 6.9 for urinary β2-MG and 4.4 for NAG in men and 8.1 for β2-MG and 6.1 for NAG μg/g creatinine (Creat) in women. These BMDLs of urinary Cd (μg/g Creat) for NAG were less than the geometric mean urinary Cd in the polluted area (6.5 in men and 7.1 in women). The estimated BMDLs of blood Cd (μg/L) were 6.2 for urinary β2-MG and 5.0 for NAG in men and 5.9 for β2-MG and 5.8 for NAG in women. The calculated BMDLs were similar or less compared with the geometric mean blood Cd (μg/L) in the polluted Thai area (6.9 in men and 5.2 in women). Conclusion: The BMDLs of urinary and blood Cd for renal effects were estimated to be 4.4 - 8.1 μg/g Creat and 4.4 - 6.2 μg/L in the Thai population aged ≥ 40 years old, suggesting that more than 40% of the residents were at risk of adverse renal effects induced by Cd exposure in Thailand. © 2014 Nishijo et al.; licensee BioMed Central Ltd.